Ação biocida do Poliquilgerm® derivado dom óleo de Ricinus Communis L. (mamona) sobre bactérias contaminantes da fermentação etanólica - Bertoletti, Ariane Christine Degasperi [UNESP] (Universidade Estadual Paulista (Unesp), 2008)
O óleo extraído das sementes de Ricinus communis L. (mamona) é um triglicerídeo rico em ácidos graxos, com a presença dominante do ácido ricinoléico, 89,5% e que confere ao óleo de mamona características peculiares. Mediante a síntese química deste óleo foi desenvolvido o Poliquilgerm® (POL), produto que segundo estudos realizados apresenta ação antimicrobiana. Como verificado em casos no campo odontológico; sobre Escherichia coli e Candida albicans, além de outros trabalhos na área de fermentação etanólica. Desta forma este trabalho teve como objetivo testar “in vitro” o POL no controle de bactérias contaminantes de dornas de fermentação e sobre a viabilidade de Saccharomyces cerevisiae, buscando assim minimizar as perdas na produção de álcool. Para a realização dos testes utilizaram-se culturas puras e mistas de S. cerevisiae, Lactobacillus fermentum e “pool” de bactérias isoladas de processo fermentativo. Analisou-se o efeito do POL sobre a viabilidade da levedura; na concentração inibitória mínima para L. fermentum; na produção de ácido lático e na fermentação. As concentrações de POL variaram conforme cada teste entre: 0; 0,5; 1; 5; 10; 20; 50; 100; 200 ppm. O POL apresentou ação microbiocida contra a levedura na concentração 200 ppm abaixo deste valor exerceu atividade microbiostática. Sobre L. fermentum concentrações acima de 50 ppm foi suficiente para eliminar a bactéria.

The oil extracted from seeds of Ricinus communis L. (castor plant) is a triglyceride rich in fatty acids, with the dominant presence of ricinoleic acid, 89.5% that gives it especial characteristics. Poliquilgerm® (POL) was developed through chemical synthesis of the oil and according to studies this product shows antimicrobial action. It was observed in cases in the odonthologic field; on Escherichia coli and Candida albicans, and also in some researches in ethanolic fermentation area. Therefore this study aimed to test the POL for in vitro control of bacteria contaminants of the fermentation process and on the viability of Saccharomyces cerevisiae, seeking thereby minimize the losses on alcohol production. Tests were done with pure and mixed cultures of S. cerevisiae, Lactobacillus fermentum and a pool of bacteria from fermentation process. The effect of POL on yeast viability; was analyzed on the minimum inhibitory concentration for L. fermentum; on production of lactic acid and on fermentation processes. Concentrations of POL varied in each test between: 0; 0.5; 1; 5; 10; 20; 50; 100 and 200 ppm. POL’s microbiocidal action was observed against yeast in the concentration of 200 ppm below this value microbiostatic activity was noticed. On L. fermentum concentrations above 50 ppm were sufficients to eliminate the bacteria. Significant reduction of lactic acid was observed with 20 ppm POL in pure cultures of bacteria contaminants and in association with S. cerevisiae, with inhibition average of 90%. Under 5 ppm concentration, there was average decrease of 50% in the production of lactic acid in all cultures studied.
Keywords: Fermentação; Agentes microbianos; Lactobacillus fermentum; Sacchoromyces cerevisiae